Schooling of people with Autism Spectrum Disorder (ASD) in adulthood: reports and perspectives of parents and caregivers of adults with ASD. - Duarte Rosa, Fernanda; Simões Matsukura, Thelma; Elisabeth Squassoni, Carolina (Brazilian Journal of Occupational Therapy / Cadernos Brasileiros de Terapia Ocupacional, 2019)
The Educational National Policy, within the perspective of inclusive education, orients teaching and learning systems to guarantee access since preschool until high school/vocational school. The literature on the field reviews the need for a greater understanding of schooling processes for people with ASD in the different stages of life. This study has aimed to identify the perspective of families of adults with ASD regarding the institutions that offer care to autistic people during adulthood. The study has also aimed to identify the educational trajectory, its positive aspects/challenges, under the outlook of their family members. The research methodology includes the provision of two questionnaires, subsequently analyzed under descriptive statistics and Collective Subject Discourse Methodology (CSD). In total, 67 parents/caregivers of adults with ASD, residents in 14 Brazilian states, were part of the study. The results reveal the exclusion experienced by these adults in their educational trajectories, since their childhood/adolescence, until their adulthood. Moreover, it is noted that most of them have been inserted only in special education institutions, with only eight reaching regular teaching institutions within adulthood. The reported challenges were related to inclusion, service quality and permanence in the educational institutions. As for positive aspects, the expansion of socialization and the gain of new skills have been highlighted. Ultimately, these family members showed their perspectives on characteristics institutions should have, in order to be considered suitable to care for people with ASD during adulthood, comprising individual and comprehensive care.